Ethnomathematical study of traditional Hole rituals in the Sabu community in Sabu Liae Sub-District Sabu Raijua District - Dominikus, Wara Sabon; Madu, Aleksius; Bale, Dian Vanita Lulu (Edelweiss Applied Science and Technology, 2025)
The uniqueness of the culture of a particular region has the potential to contain mathematical concepts, one of which is the culture of the Hole Customary Ritual in the Sabu community of Sabu Liae District, Sabu Raijua Regency. This study aims to describe the ethnomathematics in the culture of the Hole Customary ceremony and related mathematical concepts, as well as to design learning tools for the mathematical concepts found. This research was conducted in Sabu Raijua District, with four research subjects. The type of research is qualitative with an ethnographic approach, where the researcher, as the main instrument, plays a role in collecting data through interviews, observation, and documentation. Data validity uses source triangulation techniques. Data analysis uses ethnomathematics characteristics based on the Miles and Huberman model. The results showed that there is ethnomathematics in the culture of the Hole ceremony, including the activities of counting, measuring, localizing, designing, playing, and explaining. From these activities, mathematical concepts are identified, which include drawing patterns, addition, one-on-one pairing, relations and functions, comparison, and geometry. Thus, these various mathematical concepts can be developed by designing learning tools.